Contemporary Museum Strategies in Employing Digital Art: An Analytical Study on the Preservation and Display of the Digital Image - Buraq Ali Ahmed Alawadi (Indonesian Journal of Cultural and Community Development, 2026)
General Background: The integration of digital technology has transformed visual arts, giving rise to digital art and redefining museum practices. Specific Background: Contemporary museums increasingly adopt digital systems for displaying, documenting, and preserving digital images while incorporating interactive audience experiences. Knowledge Gap: Despite widespread adoption, challenges persist regarding long-term preservation, technological obsolescence, and the absence of unified digital management protocols. Aims: This study examines museum strategies in digital art display, analyzes preservation methods, and evaluates artist and institutional practices within digital museum contexts. Results: Findings reveal diverse display approaches ranging from individual screens to immersive interactive environments that facilitate direct audience engagement. However, insufficient technical expertise and lack of standardized preservation frameworks threaten the sustainability of digital artworks. Additionally, integrating educational technologies with digital exhibitions strengthens audience interaction, while structured digital governance policies support artwork continuity. Novelty: The study provides a comprehensive analytical synthesis linking display strategies, preservation challenges, and governance mechanisms within contemporary digital museums. Implications: Establishing standardized preservation protocols, strengthening technical training, and integrating educational and technological systems are essential to ensure the long-term sustainability and accessibility of digital art in museum environments. Highlights: Diverse exhibition formats enable direct visitor interaction with digital artworks. Absence of unified preservation standards risks media deterioration and data loss. Governance policies support continuity and re-exhibition of digital collections Keywords: Digital Art, Contemporary Museums, Digital Preservation, Interactive Display, Visual Arts